2019
DOI: 10.20899/jpna.5.1.95-109
|View full text |Cite
|
Sign up to set email alerts
|

Managing Volunteer Retirement among Older Adults: Perspectives of Volunteer Administrators

Abstract: A large body of quantitative evidence demonstrates a link between volunteering and improved well-being, especially among older adults. Yet the research evidence pointing to the purported benefits of volunteering does not adequately address the unique experiences of older volunteers, nor does it address the ways in which working with them impacts the work of volunteer administrators. As the proportion of those aged 65 and older increases, older adults are poised to play an even greater role as volunteers than e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Empirical studies found that volunteering participation might be helpful in improving the physical and psychological health of disabled people (Binder & Freytag, 2013;Borgonovi, 2008) as well as other marginalized or isolated groups, such as older adults (e.g., Jiang et al, 2020;Russell et al, 2019), LGBTQ+ individuals (Gates & Dentato, 2020), and the homeless (Morton & Cunning-Williams, 2009). Studies highlighted that volunteering-defined as "the act of freely doing something without remuneration that is intended to improve others' quality of life directly or indirectly, with the recipient being outside one's own household" (Cnaan & Park, 2016, p. 24)-may improve the mental health of individuals with disabilities because it makes the volunteers feel that they are physically and mentally capable of playing meaningful roles in the community (Drucker, 2006).…”
Section: Positive and Negative Effect Of Volunteering On Well-beingmentioning
confidence: 99%
“…Empirical studies found that volunteering participation might be helpful in improving the physical and psychological health of disabled people (Binder & Freytag, 2013;Borgonovi, 2008) as well as other marginalized or isolated groups, such as older adults (e.g., Jiang et al, 2020;Russell et al, 2019), LGBTQ+ individuals (Gates & Dentato, 2020), and the homeless (Morton & Cunning-Williams, 2009). Studies highlighted that volunteering-defined as "the act of freely doing something without remuneration that is intended to improve others' quality of life directly or indirectly, with the recipient being outside one's own household" (Cnaan & Park, 2016, p. 24)-may improve the mental health of individuals with disabilities because it makes the volunteers feel that they are physically and mentally capable of playing meaningful roles in the community (Drucker, 2006).…”
Section: Positive and Negative Effect Of Volunteering On Well-beingmentioning
confidence: 99%
“…The reasons for volunteer retirement may be particularly important for the well-being of older adults (e.g., Butrica et al, 2009), and the inability to include them in the present analysis is undoubtedly a limitation. For instance, whether or not individuals retire from volunteering due to circumstances that they feel are within their control (e.g., wanting to spend more time on other activities) versus circumstances that they perceive as beyond their control (e.g., health concerns, coupled with pressure from family, friends, doctors, or the organization itself), or whether this ultimately represents a permanent transition or one they decide to reverse, could play a critical role in determining the extent to which volunteer retirement is associated with declines in their well-being (Russell et al, 2019). Another factor to consider is whether or not the decision to retire from volunteering ultimately represents a permanent transition for older adults or if they look to return to the same or a substitute volunteer role at a later point in time.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Volunteer retirement is defined as the decision to withdraw from or discontinue volunteering (Russell et al, 2019). Volunteer retirement for older adults may reflect a series of complex and involuntary or voluntary events, such as failing health, lack of transportation to and from the volunteer site, or per the recommendation or encouragement of friends, family, and doctors.…”
Section: Background and Significancementioning
confidence: 99%
See 2 more Smart Citations